An analysis of mathematical modelling in Swedish textbooks in upper secondary school - Frejd, Peter (NOMAD Nordic Studies in Mathematics Education, 2013)
A new national curriculum has recently been implemented in the Swedish upper sec-ondary school where one of the goals to be taught is modelling ability. This paper presents a content analysis of 14 ”new” mathematical textbooks with the aim to investigate how the notion of mathematical modelling is presented. An analytic scheme is developed to identify mathematical modelling in the textbooks and to analyse modelling tasks and instructions. Results of the analysis show that there exist a variety of both explicit and implicit descriptions, which imply for teachers to be attentive to complement the textbooks with other material.